Comparative study of double phototherapy (conventional plus biliblanket) verses conventional single phototherapy in the management of neonatal hyperbilirubinemia (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v18i2.3826Journal of Chittagong Medical College Teachers' Association 2007: 18(2):21-25